2012
DOI: 10.1016/j.appet.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-food odorants reduce chocolate cravings

Abstract: The present study compared the relative effectiveness of simple, commercially available food and non-food olfactory tasks on chocolate craving reduction. Chocolate cravings were induced by a series of coloured photographs and 67 undergraduate women were asked to smell one of three odours (green apple, jasmine, or water). The non-food odorant (jasmine) significantly reduced chocolate cravings relative to both the food and control odorants. Thus simple non-food odorants offer potential scope as a technique for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…This prediction has been confirmed for both cigarette (May, Andrade, Panabokke, & Kavanagh, 2010;Versland & Rosenberg, 2007) and food cravings (Hamilton et al, 2013;Kemps & Tiggemann, 2007, 2009Kemps, Tiggemann, & Bettany, 2012). Other visuospatial tasks such as clay modeling out of sight (Andrade, Pears, May, & Kavanagh, 2012;May, Andrade, Panabokke, et al, 2010), playing the mobile app Tetris® (Skorka-Brown, , tapping a spatial pattern or maintaining lateral eye movements (McClelland, ) also reduce craving for these targets.…”
Section: Elaborated Imagery Is Central To Intense Desirementioning
confidence: 68%
See 1 more Smart Citation
“…This prediction has been confirmed for both cigarette (May, Andrade, Panabokke, & Kavanagh, 2010;Versland & Rosenberg, 2007) and food cravings (Hamilton et al, 2013;Kemps & Tiggemann, 2007, 2009Kemps, Tiggemann, & Bettany, 2012). Other visuospatial tasks such as clay modeling out of sight (Andrade, Pears, May, & Kavanagh, 2012;May, Andrade, Panabokke, et al, 2010), playing the mobile app Tetris® (Skorka-Brown, , tapping a spatial pattern or maintaining lateral eye movements (McClelland, ) also reduce craving for these targets.…”
Section: Elaborated Imagery Is Central To Intense Desirementioning
confidence: 68%
“…Even passive exposure to sensory stimuli can disrupt imagery and craving. Examples are odors (Kemps & Tiggemann, 2013b;Kemps et al, 2012) and dynamic visual noise (changing patterns of black/white squares on a screen; Kemps, Tiggemann, & Christianson, 2008;May, Andrade, Panabokke, et al, 2010;McClelland et al, 2006;Steel, Kemps, & Tiggemann, 2006).…”
Section: Elaborated Imagery Is Central To Intense Desirementioning
confidence: 99%
“…It remains to be seen as to which specific odours might provide the best craving reduction stimulation. Here we used a neutral unfamiliar odour, and a recent paper has suggested that a non-food odour would be more effective than a food odour Odours reduce food cravings 13 (Kemps, Tiggemann & Bettany, 2012). Future research also needs to determine how long the craving reducing effect will last, given that people may habituate to odours quite quickly.…”
Section: Discussionmentioning
confidence: 99%
“…After being received by the primary olfactory cortex, olfactory signals reach the secondary olfactory cortex, including the insula and OFC, as well as the hypothalamus (which is implicated in the maintenance of homeostasis), and the amygdala (which is implicated in emotion appraisal). Perhaps because of the connections between efferent fibers from the olfactory bulb and structures such as the entorhinal cortex, OFC, amygdala, and insula, olfactory stimulation is known to elicit vivid recall of past memories and induction of various emotional states [17], and can also moderate subjective food craving [18]. …”
Section: Neuroanatomy Of the Gustatory And Olfactory Pathwaysmentioning
confidence: 99%